2013
DOI: 10.5604/20815735.1090669
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency and stress experience among judo and taekwondo athletes

Abstract: Researchers frequently deliberate why some people are resistant to life difficulties whereas others develop negative health effects (physical or psychical). With this respect, the notion of resiliency has been introduced as an attempt to answer this question. The majority of authors, beginning with the creators of this concept [1,2], treat resiliency as a relatively stable disposition of a unit. It is also reported that it is a resource that more often appears as a result of experiencing serious difficulties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
4
Order By: Relevance
“…En lo correspondiente a los factores resilientes se observan puntuaciones en un nivel medio (CP: M = 100, SD = 12.4; ASMV: M = 42, SD = 7.8) en los boxeadores analizados, que difiere un poco con estudios previos con deportistas de combate que presentaron niveles más elevados en su perfil resiliente (Litwic-Kaminska, 2013;Reche-García et al, 2020). Una posible explicación radica en la mayor dificultad de adaptabilidad ante las situaciones estresantes en el periodo pandémico, incluso realizando las actividades físico-deportivas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En lo correspondiente a los factores resilientes se observan puntuaciones en un nivel medio (CP: M = 100, SD = 12.4; ASMV: M = 42, SD = 7.8) en los boxeadores analizados, que difiere un poco con estudios previos con deportistas de combate que presentaron niveles más elevados en su perfil resiliente (Litwic-Kaminska, 2013;Reche-García et al, 2020). Una posible explicación radica en la mayor dificultad de adaptabilidad ante las situaciones estresantes en el periodo pandémico, incluso realizando las actividades físico-deportivas.…”
Section: Discussionunclassified
“…De manera más específica, en lo que respecta a los deportes de combate, su práctica representa un nivel elevado de exigencia física y psicológica (Ziv & Lidor, 2013) siendo altos los niveles de presión y estrés que experimentan (Sterkowicz et al, 2012;Sterkowicz-Przybycieñ & Grygiel, 2014). Por esta razón, el estudio de la resiliencia como un factor preventivo dentro de estas disciplinas deportivas es pertinente (Litwic-Kaminska, 2013). Siguiendo esta línea, trabajos recientes reportan que los deportistas de combate presentan niveles más altos de resiliencia que los de otras disciplinas, reflejando características psicológicas positivas como autoconfianza, autonomía y sentido de persistencia (Reche-García et al, 2020), coincidiendo con los hallazgos de otros estudios (Fletcher & Sarkar, 2012;Galli & Vealey, 2008), que además señalan una capacidad para manejar mejor el estrés.…”
Section: Introductionunclassified
“…Salvador et al [ 25 ] have described anticipatory cortisol responses to competition and suggested that they are connected with the psychological preparation for competition, self-confidence, and motivation for success. Litwic-Kamińska [ 26 ] suggests that taekwondo and judo athletes from the Polish population are characterized by high resiliency, which makes them more resistant to stress. This could explain a significantly higher increase in the noradrenaline level in the karate group, but with regard to the testosterone level, such an association has been found in some athletes only.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate self-esteem and appropriate motivation allow for achieving high sports results as one’s goals [ 22 , 23 ]. In order to achieve a specific goal, an individual focuses on it until he or she achieves it [ 3 , 24 ].…”
Section: Introductionmentioning
confidence: 99%